2019
DOI: 10.1186/s13046-019-1377-7
|View full text |Cite
|
Sign up to set email alerts
|

Correction to: Synergistic killing effects of homoharringtonine and arsenic trioxide on acute myeloid leukemia stem cells and the underlying mechanisms

Abstract: In the publication of this article [1], there are two corrections.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 1 publication
1
0
0
Order By: Relevance
“…The combined application of ATO and homoharringtonine can significantly increase the apoptosis rate of Kasumi-1 cells (Tan et al, 2019), which is consistent with the results of ATOpromoting KG-1a cell apoptosis in this study (Figures 1B,D). The q-PCR results showed that the proapoptotic genes BAX and BAD were significantly up-regulated, whereas the inhibitory apoptosis gene BCL2L1 was significantly down-regulated (Figure 4A).…”
Section: Discussionsupporting
confidence: 91%
“…The combined application of ATO and homoharringtonine can significantly increase the apoptosis rate of Kasumi-1 cells (Tan et al, 2019), which is consistent with the results of ATOpromoting KG-1a cell apoptosis in this study (Figures 1B,D). The q-PCR results showed that the proapoptotic genes BAX and BAD were significantly up-regulated, whereas the inhibitory apoptosis gene BCL2L1 was significantly down-regulated (Figure 4A).…”
Section: Discussionsupporting
confidence: 91%